A finalização em aquarela dos livros iluminados de William Blake: por uma metodologia de análise da arte compósita - Cabrera, Ana Paula (2015)
This thesis analyzes the creation process of the illuminated books by William Blake and its interpretative effects. The main objective is to analyze the books from this artist who produced his work by a mixed method which included recording with acids on copper plates, traditional printing on linen paper and finishing with watercolor. In order to unravel the trials we observe the printing technique and application of color on each copy of the illuminated books. The first chapter seeks to answer the question: What is color? Therefore, we will divide this chapter into two sections. The first section of this chapter, we present the history of color and the problem of copies of illuminated with different color finishes books. The question that guides the next section is: what’s the Blake technique? Blake explain the technique in relation to copper plate, engraving with acids and the printing method. In the second chapter we will discuss what is the technique of watercolor in the context of the eighteenth and nineteenth century, where Blake was inserted and how this kind of painting was used by Blake, analyzing the copies of the illuminated books and its interpretative effects. After this contextualization in the third chapter we will interpret the colors. Our object of study are the colors: red, blue and yellow.These colors have been most used by Blake. Thus, in the following sections we will discuss the colors explaining the difference of color printing. In it, we will describe a methodological analysis contrasting two copies from different periods. The second section of the chapter will deal with the red color and its meaning in Blake work. Our analysis methodology is to study two copies of illuminated books from different periods, addressing the conceptual point of view of that color. The chapter studies then the colors blue and yellow. We will address both colors in the following sections, where we will observe the effect of each of these, as well as their images and the visual details that comprise each of the plates. In the work of William Blake color makes sense, it represents feelings and sensations that blend the mystical and prophetic context exacerbated by his poetic genius, we are led to the world of color imagery. With its creative power this singular artist shows in his work a unique style that reflects the variety of life and prints. As critical and theoretical foundation will use authors that discuss the relationship between text and image in Blake’s art such as Michael Phillips, Joseph Viscomi, Robert Essick, Manuel Portela, Enéias Tavares, between other critics beyond color scholars such as, Joyce Towsend, J. Bamz, Roy Osborne, Jaqueline Lichtenstein and Goethe.